Game Theory for Networks 2nd International ICST Conference, GAMENETS 2011, Shanghai, China, April 16-18, 2011, Revised Selected Papers - Jain, Rahul; Kannan, Rajgopal; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Game Theory for Networks (GameNets 2011) held in Shanghai, China, April 16-18, 2011. The 45 revised full papers presented were carefully selected from numerous submissions and focus topics such as mechanism design, physical layer games, network mechanisms, stochastic and dynamic games, game-theoretic network models, cooperative games in networks, security games, spectrum sharing games, P2P and social networks and economics of network QoS.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).